The Influence of Tarbawi Tafsir in the Islamic Boarding School Environment and Salafiyyah Educational Values - Zaenal Mufid; Iskandar Mirza (Penerbit Hellow Pustaka, 2025)
This research discusses the influence of tarbawi interpretation on the education of Salafiyyah values in Islamic boarding schools. Tarbawi interpretation is an approach to understanding the Qur'an that focuses on educational aspects and holistic character formation, including cognitive, social, spiritual and emotional dimensions. In the context of Islamic boarding schools, this approach is used to instill the values of faith (i'tiqadiyah), the practice of worship (amaliyah), and noble morals (khuluqiyah) in students. This research uses a descriptive qualitative method with a literature study approach, which refers to classical and contemporary books of interpretation, as well as studies related to Islamic education. The research results show that tarbawi interpretation is able to increase students' understanding of Islamic values, strengthen character, and encourage the application of Islamic teachings in everyday life. The application of tarbawi interpretation in Islamic boarding schools also has a positive impact on creating a learning environment that is meaningful, participatory and conducive to the personal and social development of students. In addition, through this approach, educators can integrate the values of the Koran into learning activities, either through exemplary methods, habituation or deliberation. Thus, tarbawi tafsir makes a significant contribution to realizing the goals of Islamic education that are comprehensive and relevant to the challenges of the times.